Microscopic and geochemical analyses of the Tonian Longfengshan biota from the Luotuoling Formation (Hebei Province, North China) with taphonomic implications - Jing, Y; Chen, Z-Q; Anderson, RP; Wang, X; Zheng, Z; Feng, X (Elsevier, 2022)
The Tonian Longfengshan biota is among the earliest known fossil assemblages with a predominance of the benthic macroalgal fossil Longfengshania Du, 1982, which is well known for its blade, stipe, and holdfast differentiation. However, the microstructure and geochemical composition of these fossils are poorly understood. We documented the microscopic characteristics, mineralogy, and geochemistry of 29 fossil specimens from the Luotuoling Formation at the Longfengshan locality of Hebei Province, North China using scanning electron microscopy (SEM), energy dispersive X-ray spectroscopy (EDS), micro X-ray fluorescence spectroscopy (μ-XRF), Raman spectroscopy, and X-ray Diffraction (XRD). SEM-EDS revealed that all fossil specimens are preserved as two-dimensional compressions that are composed of carbonaceous patches and also have high calcium content. Iron-rich clay minerals were additionally detected in association with the fossils. μ-XRF mapping confirmed the fossils’ high calcium content. Raman spectroscopy showed that carbonaceous patches are comprised of disordered organic carbon that has been altered by low grade metamorphism (<300 °C). XRD showed a homogenous mineralogy (dominated by quartz, feldspar, and muscovite with other minor e.g., kaolinite, smectite). Petrographic analysis revealed that microbial mats existed in the fossil-bearing shale, implying that benthic macroalga Longfengshania attached its holdfast in a sticky microbial mat that encrusted the sea-bed. Integration of these data suggested that the fossil-bearing silty shale was deposited in the subtidal zone below storm wave base. Iron-replete but sulfate-depleted porewater within sediments may have inhibited the degradation process of the Longfengshan macroalgae.